2005
DOI: 10.1002/prot.20378
|View full text |Cite
|
Sign up to set email alerts
|

Induced refolding of a temperature denatured llama heavy‐chain antibody fragment by its antigen

Abstract: In a previous study we have shown that llama VHH antibody fragments are able to bind their antigen after a heat shock of 90°C, in contrast to the murine monoclonal antibodies. However, the molecular mechanism by which antibody:antigen interaction occurs under these extreme conditions remains unclear. To examine in more detail the structural and thermodynamic aspects of the binding mechanism, an extensive CD, ITC, and NMR study was initiated. In this study the interaction between the llama VHH -R2 fragment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 26 publications
2
57
0
Order By: Relevance
“…In addition to its high binding capacity, VHH has several attractive features, such as resistance to pepsin, acid environment, and heat (26,27). Furthermore, because of its small size and simple form, it is easy to produce VHH as a recombinant protein with an intact spatial structure (28).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its high binding capacity, VHH has several attractive features, such as resistance to pepsin, acid environment, and heat (26,27). Furthermore, because of its small size and simple form, it is easy to produce VHH as a recombinant protein with an intact spatial structure (28).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their single domain character, standard molecular biology techniques such as PCR allow for easy selection of appropriate Nanobody candidates from the full antibody repertory of immunized animals (12). Nanobodies show a high solubility and a good capacity to refold after denaturation while retaining their binding capacity (13,14). Particularly attractive is the flexibility of drug formatting whereby it is straightforward to generate multivalent and/or multispecific single-molecule formats and to produce these formats in bacteria and yeast (13,15).…”
Section: Introductionmentioning
confidence: 99%
“…These features may render 3F5 exceptionally unstructured in absence of its epitope. Previously, it was shown that antigens can induce structural changes on a thermically denatured HCAb [11]. In 3F5 such structural changes are detectable without the need to denature the protein, which may be attributable to the dynamic nature of all three CDRs in 3F5.…”
Section: Discussionmentioning
confidence: 97%
“…In OPMD patients the (GCG) 6 moiety is expanded to (GCG) [8][9][10][11][12][13] , generating instead of 10 alanines an array of 12-17 alanines [4]. This multi-domain protein also contains a glutamate rich N-terminal domain essential for the stimulation of the poly(A)polymerase, an a-helix domain of $30 amino acid residues (Leu119-Gln147), an RNA binding domain and an arginine rich C-terminal domain [6].…”
Section: Introductionmentioning
confidence: 99%